2014
DOI: 10.1186/1746-1596-9-72
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of HLA EMR8-5 immunohistochemically analyzed expression in osteosarcoma

Abstract: BackgroundDefects in Human Leukocyte Antigen (HLA) class I antigen expression and/or function in tumor cells have been extensively investigated, because of their potential role in the escape of tumor cells from T cell recognition and destruction. The researchers evaluated HLA class I expression in tumor tissue as a prognostic factor in osteosarcoma patients and as a predictor of their survival. This retrospective cohort study was conducted at the pathology laboratory of Ain Shams University Hospital, and Ain S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…Importantly, and despite the limited number of patients, HLA class I expression in primary osteosarcomas correlated with a better disease-free survival, which is consistent with previous results [16, 17]. In addition, we observed that HLA class I expression in metastases was frequently positive, and this was in contrast to Tsukahara et al [17] who reported that HLA class I loss or down-regulation occurred more commonly in metastatic osteosarcoma lesions (7 out of 8 cases; 88%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, and despite the limited number of patients, HLA class I expression in primary osteosarcomas correlated with a better disease-free survival, which is consistent with previous results [16, 17]. In addition, we observed that HLA class I expression in metastases was frequently positive, and this was in contrast to Tsukahara et al [17] who reported that HLA class I loss or down-regulation occurred more commonly in metastatic osteosarcoma lesions (7 out of 8 cases; 88%).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, we observed defects in HLA class I expression in 44% of the osteosarcomas, mainly with a heterogeneous pattern instead of a complete lack of HLA class I. Previous studies have reported a loss or a down-regulation of HLA class I expression in approximately 50–62% of osteosarcomas, using a pan-HLA class I antibody (EMR8-5) and a cut-off of 50% positive tumour cells [16, 17]. In our series, negative or heterogeneous expression of HLA-A molecules was found more frequently compared to the other heavy chains HLA-B/C and β2-microglobulin.…”
Section: Discussionmentioning
confidence: 56%
“…Conventional factors, such as pathological clinical stages and metastasis, are important predictors of poor clinical outcome of osteosarcoma in clinical practice. Furthermore, a number of less common molecular markers have also shown prognostic roles, such as Mediator of RNA polymerase II transcription subunit 19 (Med19), microRNA-9 (miR-9), and human leukocyte antigen (HLA) class I antigen expressions [25][26][27]. However, these markers are only available following surgery or their measurement is complex, and therefore, they are often not used in clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…The loss of HLA I expression was recently shown in 39% of undifferentiated pleomorphic sarcomas, 80% of fibrosarcomas, and 88% of dermatofibrosarcomas . For patients with osteosarcomas and high levels of expression of class I MHC/HLA molecules, compared with patients with no expression, overall survival and event‐free survival significantly improved . Regarding Ewing's sarcoma, loss of HLA expression was shown in 79% of Ewing's tumors .…”
Section: Methodsmentioning
confidence: 99%